Discovery of new indole-based acylsulfonamide Nav1.7 inhibitors. Issue 4 (15th February 2019) - Wu, Yong-Jin; Venables, Brian; Guernon, Jason; Chen, Jie; Sit, Sing-Yuen; Rajamani, Ramkumar; Knox, Ronald J.; Matchett, Michele; Pieschl, Rick L.; Herrington, James; Bristow, Linda J.; Meanwell, Nicholas A.; et al.
Graphical abstract: Abstract: Screening of 100 acylsulfonamides from the Bristol-Myers Squibb compound collection identified the C3-cyclohexyl indole6 as a potent Nav 1.7 inhibitor. Replacement of the C2 furanyl ring of6 with a heteroaryl moiety or truncation of this group led to the identification of 4 analogs with hNav 1.7 IC50 values under 50 nM. Fluorine substitution of the truncated compound12 led to34 with improved potency and isoform selectivity. The inverted indole36 also maintained good activity. Both34 and36 exhibited favorable CYP inhibition profiles, good membrane permeability and a low efflux ratio and, therefore, represent new leads in the search for potent and selective Nav 1.7 inhibitors to treat pain.